HUBUNGAN KEAKTIFAN SENAM LANSIA DENGAN KESEIMBANGAN TUBUH PADA LANSIA DI PANTI WERDHA MAJAPAHIT MOJOKERTO - Ariu Dewi Yanti; Lufita Armayanti (STIKes William Booth Surabaya, 2016)
Decrease in balance on the elderly can be fixed with various exercise balance. A good balance is needed someone in support to its mobility it everyday. The purpose of this research was to know relationship liveliness following the elderly exercisers with body balance on the elderly in Panti Werdha Majapahit Mojokerto. This Research design was analytic correlational with cohort study approach. The variable are the lifelines following a gymnastic for elderlyas independent variable and the balance of elderly body as dependent variables. This Population were all of elderly in Panti Werdha Majapahit Mojokerto as much as 47 elderly. Samples taken with purposive sampling technique as many as 24 respondents. Data collected with observation sheet about follow gymnastics and questionnaire of berg balance scale then tested with spearman rhotest. Spearman rho test results showed that’s ρ = 0,008, α = 0,05 so that’s ρ < αexplained that there is a connection between liveliness of gymnastics with elderly body's balance. The results showed that the more active elderly to follows the gymnastics it will be increasing their independent or well balance their body.This happens because the elderly exercisers indirectly will keep your muscles and joints in order not to experience a decrease in function that will have an impact on the drop in its ability to support the mobility of the elderly. Expected for health care personnel to be more active in the evocativespirit of elderly in following gymnastics by giving a gift or an award on the elderly are active so they are more motivated to follow gymnastics elderly.